The Influence of Capital Structure, Dividend Policy and Inflation on Company Value with Profitability as an Intravenant Variable in Banking Companies Listed on the Indonesian Stock Exchange in 2019-2023 - Maulina Febrianti; Susanti Widhiastuti (GoodWill, 2026)
This study aims to analyze the factors that have influenced capital structure, dividend policy, and inflation on company value with profitability, both simultaneously and partially, with the factors that will be tested in this study being capital structure, dividend policy, and inflation. The type of data to be used is secondary data that will be sourced from financial reports that have been published through the Indonesia Stock Exchange website. The population that will be used in this research is all banking companies that have been registered on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with the number of companies totaling 35 companies, and the sampling method that will be used is purposive sampling. The data collection method that will be used is documentation, with data collection techniques through articles, journals, and published financial reports. The results of this study show the following: 1) Capital structure has an influence on profitability, 2) Dividend policy has an influence on profitability, 3) Inflation has no influence on profitability, 4) Capital structure has no influence on company value, 5) Dividend policy has an influence on company value, 6) Inflation has no influence on company value, 7) Profitability has an influence on company value, 8) There is no influence of capital structure on company value through profitability, 9) There is no influence of capital structure on company value through profitability, and 10) There is no influence of inflation on company value through profitability.